2019
DOI: 10.15760/trec.220
|View full text |Cite
|
Sign up to set email alerts
|

How Can Interdisciplinary Teams Leverage Emerging Technologies To Respond To Transportation Infrastructure Needs? A Mixed-Methods Evaluation of Civil Engineers, Urban Planners, and Social Workers’ Perspectives

Abstract: How can interdisciplinary teams leverage emerging technologies to respond to transportation April 2019 infrastructure needs? A mixed-methods evaluation of civil engineers, urban planning, and social workers' perspectives. 6. Performing Organization Code

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[15] found that the lack of reliable and affordable public transportation is a significant barrier to the use of public transportation in Jakarta. Studies [13], [16] also found that improving public transport systems and promoting the use of active modes of transport such as walking and cycling can be effective strategies to reduce the use of personal transport and improve public health.…”
Section: Transportationmentioning
confidence: 99%
“…[15] found that the lack of reliable and affordable public transportation is a significant barrier to the use of public transportation in Jakarta. Studies [13], [16] also found that improving public transport systems and promoting the use of active modes of transport such as walking and cycling can be effective strategies to reduce the use of personal transport and improve public health.…”
Section: Transportationmentioning
confidence: 99%
“…Sustainable urban design is an interdisciplinary field that involves architecture, urban planning, environmental engineering, and sociology. The University of Texas at Arlington offers a unique interdisciplinary course on sustainable urban design that equips students with the skills to navigate complex urban design decision-making milieus (Fields et al, 2019;Repko, 2009). The course examines the history of urban design, form, and infrastructure in various cities to provide students with an understanding of how decisions about design impact the lives of inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…In medicine, multidisciplinary teams can more effectively relieve the pain, symptoms, and stress experienced by patients with serious illnesses [3]. To build transportation systems that equitably serve communities, transportation planners and engineers are being called to collaborate with social workers and the communities they serve [4]. To develop artificial intelligence systems with effective human-AI interaction, collaboration is needed between computer scientists, systems engineers, human factors engineers, and socio-technical researchers [5].…”
Section: Introductionmentioning
confidence: 99%